2011
DOI: 10.1177/0194599811402030
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Gene Expression in the Sinonasal Cavity of Patients with Chronic Sinusitis with Polyps

Abstract: Objective To determine whether variations in gene expression exist at multiple subsites along the sinonasal tract in patients with chronic sinusitis with polyps and in healthy controls. Study Design Prospective, controlled study. Setting Academic medical center. Subjects and Methods Tissue expression levels of 5 genes, previously found to be characteristic of ethmoid polyps, were measured using real-time quantitative polymerase chain reaction in 100 sinonasal tissue samples. Specimens harvested from 5 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
1
32
2
Order By: Relevance
“…Although a history of asthma has been associated with both the presence of nasal polyps and their recurrence, in the current study asthma was not found to impact the time to revision sinus surgery in patients with CRSwNP. Severity of CT stage was also not found to be a significant factor in predicting time to revision surgery.…”
Section: Discussioncontrasting
confidence: 66%
“…Although a history of asthma has been associated with both the presence of nasal polyps and their recurrence, in the current study asthma was not found to impact the time to revision sinus surgery in patients with CRSwNP. Severity of CT stage was also not found to be a significant factor in predicting time to revision surgery.…”
Section: Discussioncontrasting
confidence: 66%
“…This was confirmed through the implementation of 2 distinct identification techniques, sq-RT-PCR and immunofluorescence. Although sq-RT-PCR has been widely used in past studies, 9,10 this is also the first time, to our knowledge, that immunofluorescence labeling and confocal microscopy has been used to detect periostin protein in sinonasal tissue. This allowed for another method by which to validate periostin's presence in sinonasal tissue and as well as relatively quantify it across tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…9 These increased periostin levels were found to be specific to the polypoid tissue sample itself and not universally elevated in samples of adjacent "healthy" mucosa from the same patient. 10 However, despite periostin's significant role in Th-2-mediated pathways, eosinophil recruitment, mucus production, and sinonasal inflammatory disease, it has yet to be evaluated in patients with AFRS.…”
mentioning
confidence: 99%
“…Recent attempts to identify inflammatory endotypes have presented a more nuanced approach to the classification of CRS, with Tomassen et al recently using surgically-obtained tissue to identify potential CRS endotypes based entirely on inflammatory biomarkers 4 . While such studies have preferentially used tissue-based assessment of inflammatory mediators, this approach may have some logistical limitations as it is inherently invasive and subject to variations in site-specific protein expression throughout the sinonasal cavity 5, 6 . Minimally invasive approaches to disease endotyping have been reported for asthma and other respiratory diseases, typically employing analysis of sputum, mucus, or epithelial brushings 79 .…”
Section: To the Editormentioning
confidence: 99%